2015
DOI: 10.1620/tjem.236.81
|View full text |Cite
|
Sign up to set email alerts
|

Neurofeedback Training Improves the Dual-Task Performance Ability in Stroke Patients

Abstract: Owing to the reduced capacity for information processing following a stroke, patients commonly present with difficulties in performing activities of daily living that combine two or more tasks. To address this problem, in the present study, we investigated the effects of neurofeedback training on the abilities of stroke patients to perform dual motor tasks. We randomly assigned 20 patients who had sustained a stroke within the preceding 6 months to either a pseudo-neurofeedback (n = 10) or neurofeedback (n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 40 publications
0
23
0
1
Order By: Relevance
“…Table 2 shows participant characteristics, wearable devices, type of sensors and placement, experimental and control intervention, timing of the intervention, balance and gait outcomes, and finally time points of the included studies. The selected RCTs were performed in people with PD (n = 6) [ 40 , 41 , 42 , 43 , 44 , 45 ], stroke (n = 13) [ 41 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ] and mild cognitive impairment (MCI) (n = 1) [ 58 ]. The total sample consists of 513 PwND with mean age ranging from 46 to 79 years.…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 shows participant characteristics, wearable devices, type of sensors and placement, experimental and control intervention, timing of the intervention, balance and gait outcomes, and finally time points of the included studies. The selected RCTs were performed in people with PD (n = 6) [ 40 , 41 , 42 , 43 , 44 , 45 ], stroke (n = 13) [ 41 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ] and mild cognitive impairment (MCI) (n = 1) [ 58 ]. The total sample consists of 513 PwND with mean age ranging from 46 to 79 years.…”
Section: Resultsmentioning
confidence: 99%
“…The observed qEEG findings and its relationship with measurements of mood and emotions offers the possibility to be used as markers for treatment by EEG biofeedback entrainment, as it has been shown to be useful in stroke and memory impairment (Nelson, 2007), information processing (Lee et al, 2015), and motor function rehabilitation (Yilmaz et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Plummer-D'Amato et al (2007) reported positive effects on velocity, stride length and cadence applying gait training with three cognitive tasks in stroke patients [36]. Lee et al (2015) showed that gait ability (velocity, cadence, stance phase) was improved in the group treated neurofeedback training with visual stimulation in stroke patients [11].…”
Section: Discussionmentioning
confidence: 99%
“…Interventions such as neurofeedback training and action observation training have been reported to improve the concentration of brain injured patients [11][12][13][14]. These interventions have been reported to improve motor function through improved concentration, but the application of these interventions in clinical practice is not easy [6].…”
Section: Introductionmentioning
confidence: 99%